Effectiveness of Bowel Management Program for Functional Constipation in Children: Bowel Management Program - Aslam, Sana; Majid, Fatima; Kumari, Nitu; Khahro, Adnan Ali; Zamir, Naima; Anwar, Muhammad (Pakistan Journal of Health Sciences, 2023)
Functional constipation (FC) is a common problem in childhood, with an estimated prevalence of 3% worldwide. Objective: To determine the effectiveness of bowel management program in children with functional constipation. Methods: This quasi-experimental study was conducted at Department of Pediatric Surgery, NICH, Karachi, from September 2019 to November 2021. 91 children were included in the study. Informed consent was taken. A plain X-ray abdomen prior to the start of bowel management program was done to assess the fecal loading in the colon. Effectiveness of program was assessed in terms of stool frequency of 1, 2 per day and non-loading of rectum radiologically after one month of treatment. High dose laxatives were started after the patient had recovered from the first impact in older kids who had previously completed toilet training but now suffer soiling from faux incontinence or severe constipation without soiling. Daily big volume enemas were used in children who had never been toilet trained, had a history of soiling, or had a megarectum. Results: The mean age was 5.26 ± 2.20 years (95% confidence interval [CI]: 4.80-5.72), the mean weight was 17.49 ± 3.24 kg (95% CI: 16.82-18.17), the mean height was 107.27 ± 19.32 cm (95% CI: 103.24-111.29). The average duration of functional constipation was 88.11 ± 68.79 days (95% CI: 73.78-102.44). In terms of gender distribution, 63 (69.2%) patients were male, while 28 (30.8%) were female. Conclusions: The results of this study provide evidence that a bowel management programme is successful in treating functional constipation in young children.